Artificial everyday creativity: creative leaps with AI through critical making. Issue 4 (2nd October 2022) - Reddy, Anuradha
ABSTRACT: The capabilities of humans and AI systems to be creative and perform alongside one another have given rise to new practices of 'artificial creativity'. In this article, I argue that artificial creativity demonstrates the potential to empower individuals to interface and critically dialogue with computational systems. Reframed as artificial 'everyday' creativity, I focus on the curious, joyful and adjacent modes of everyday creativity by including hybrid materials that embrace alternative pedagogies of code and computation. Through the interdisciplinary design approach of 'critical making', I craft two unconventionally-coded artefacts that dialogue with AI systems, namely CryptoCrochet-Key and Internet of Towels . Both artefacts are analysed using a four-pronged creativity framework to understand the material translation processes in the artificial everyday creativity practice. With rising concerns about AI's role in misinformation, bias and discrimination, the discussion explores the generative value and limitations of artificial everyday creativity towards the broader goals of civic data literacy and user empowerment.